2020
DOI: 10.15243/jdmlm.2020.081.2491
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of level soil bund and soil bund age on selected soil physicochemical properties in Somodo Watershed, Jimma Zone, SouthWestern Ethiopia

Abstract: This study was conducted to investigate the effect of level soil bund stabilized with Vetiver grass and soil bund age on selected soil physicochemical properties on Somodo watershed, Jimma Zone, Southwestern , Ethiopia. A reconnaissance survey was conducted to identify a representative sampling site. From the selected sampling site croplands with level soil bund aged three years, six years and adjacent untreated cropland were identified. A total of 108 composite soil samples (3 treatments * 6 replications * 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Te reason for the presence of a higher proportion of sand particles in the upper catchment could be related to the resistance of the coarser fractions to detachment by runof. Similar results indicated that sand and clay fractions showed a signifcant diference with the age of SWC practice and compared with adjacent nonconserved cultivated land [23]. However, no signifcant variation in the soil particle size fraction between conserved and nonconserved cultivated land was reported [24].…”
Section: Discussionsupporting
confidence: 55%
“…Te reason for the presence of a higher proportion of sand particles in the upper catchment could be related to the resistance of the coarser fractions to detachment by runof. Similar results indicated that sand and clay fractions showed a signifcant diference with the age of SWC practice and compared with adjacent nonconserved cultivated land [23]. However, no signifcant variation in the soil particle size fraction between conserved and nonconserved cultivated land was reported [24].…”
Section: Discussionsupporting
confidence: 55%
“…The means monthly temperature of the site is 19.27°C ranging from 13.6°C and 25°C ( Fig 2 ). Nitisols is the most dominant soil type and sandy clay loam is the textural soil class of the watershed [ 21 ]. Nitisols are well drained, red or reddish soils with diffuse horizon boundaries and a nitic horizon with more than 30% clay [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nitisols and Orthic Acrisols are the most dominant soil types of the area and Nitisols accounting for 64% of slightly acidic soil [ 17 ]. The textural class of the soil is sandy clay loam, while the pH is found to be strongly acidic [ 18 ].…”
Section: Methodsmentioning
confidence: 99%